Faktor-Faktor di Balik Penangguhan Aksesi Kosovo ke Uni Eropa: Perspektif Keputusan Kolektif - Puspitaningrum, Dinda; Yuniarti (Department of International Relations, Brawijaya University, 2024)
The opportunity for membership expansion and the economic and political integration that was offered by the EU, Kosovo decided to join the EU. However, Kosovo's integration process into the European Union is still suspended due to several factors. Therefore, this research aims to explain the reason of the European Union has suspended Kosovo's membership application. This research uses an explanatory method with primary and secondary data. The data analysis technique used in this research is qualitative. This research uses the Decision-Making theory of Richard C. Snyder, H. W. Bruck and Burton Sapin. Research results show that the EU's decision to suspend Kosovo's membership application was influenced by internal and external factors. This internal factor is related to the normative values adopted by the European Union, which requires a unanimous decision of the European Council consisting of the heads of EU member states. However, there were 5 countries that rejected Kosovo's membership application proposal, namely Spain, Greece, Cyprus, Romania, and Slovakia because the five countries did not recognize Kosovo's sovereignty. Then there are external factors related to the Serbia-Kosovo conflict. After these considerations, the European Union suspended Kosovo's membership application. The European Union also supports the progress of Kosovo's accession process which is accompanied by the normalization of Kosovo-Serbia relations. The normalization of the Kosovo-Serbia relationship will also provide changes in the decisions of the five EU member states related to the recognition of Kosovo's sovereignty.